Composite additive, method for preparing concrete mixture from composite additive and application of composite additive

By using composite additives of polyester fiber, basalt fiber and calcium sulfaluminate type expansion agent in concrete, the problem of difficult to take into account both the sulfate corrosion resistance and mechanical properties of concrete in the prior art is solved, and the effect of significantly improving crack resistance and corrosion resistance is achieved, while reducing construction costs.

CN119683892APending Publication Date: 2025-03-25HOHAI UNIV SUZHOU RES INST +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411849456.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

While improving the sulfate corrosion resistance of concrete, it is difficult to maintain good mechanical properties, and commonly used methods have problems such as high energy consumption, high cost, many types of materials, and difficult preparation.

Method used

Compound additives, including polyester fiber, basalt fiber and calcium sulfaluminate type expansion agent, are used to ensure that these fibers and expansion agents are evenly distributed inside the concrete, thereby improving the resistance to sulfate corrosion.

Benefits of technology

It significantly improves the crack resistance and sulfate corrosion resistance of concrete, while reducing construction costs, reducing the strength variance of concrete, and improving the strength and durability of each age.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119683892A_ABST
    Figure CN119683892A_ABST
Patent Text Reader

Abstract

The invention discloses a composite additive as well as a method for preparing a concrete mixture and application thereof. The composite additive comprises polyester fibers (PF), basalt fibers (BF) and a calcium sulphoaluminate expanding agent (U-shaped expanding agent), the concrete mixture is prepared by mixing the composite additive and a standard concrete component. The preparation method of the composite additive and the concrete mixture is applied and verified in engineering practice and is completely suitable for preparation of common sulfate-resistant concrete, the sulfate corrosion resistance of the concrete prepared by the preparation method is remarkably improved, the mass loss rate of the concrete is reduced by 20% or above under the conditions of multiple dry-wet cycles and complex construction sites, and the sulfate corrosion resistance of the concrete is greatly improved. And the method has good robustness. According to the preparation method of the composite additive and concrete mixture, an internal material capable of resisting sulfate corrosion can be provided for common concrete, the internal material is fused in the concrete, and the problem that the sulfate corrosion resisting effect of traditional concrete is poor is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of concrete, and in particular relates to a composite additive and a method for preparing a concrete mixture and an application thereof. Background Art

[0002] As a widely used building material, concrete has become an indispensable basic material in modern engineering due to its high strength, good durability and relatively low cost. However, in a high sulfate environment, concrete is easily corroded, resulting in strength loss, cracking and spalling, which seriously affect its service life and safety. Traditional anti-sulfate erosion measures, such as the use of low-aluminate tricalcium cement, the addition of fly ash and mineral powder, etc., can improve the erosion resistance of concrete to a certain extent, but often reduce the mechanical properties of concrete. Therefore, it is particularly important to develop a new type of concrete that can not only improve the sulfate erosion resistance of concrete but also maintain good mechanical properties.

[0003] Chinese patent document CN118005365A proposes to add 8% to 12% PBL powder to fresh ordinary Portland cement concrete to improve the concrete's sulfate erosion resistance. However, this method requires magnesite and limestone as grinding aids for phosphogypsum, and grinding according to the dry basis mass ratio of phosphogypsum, magnesite and limestone is 4:2:1 to obtain PBL powder. This method has high energy consumption and high cost, does not meet the needs of engineering practice, and is difficult to promote and implement. Chinese patent CN118388183A proposes to add tailings, water glass, barium salt, chloroprene latex, and latex modifier raw material components to concrete production to improve concrete's sulfate erosion resistance. However, the material types used in this method are many and difficult to prepare, which increases the number of engineering processes and makes it difficult to promote. Chinese patent CN116535151A proposes to improve the internal pore structure and interface of concrete based on modified plant fibers and sulfate resistant agents, but plant fibers are easily corroded and have a short lifespan. After losing their function, they will become impurities left in the concrete, affecting the subsequent strength of the concrete. Obviously, they are not suitable for the actual working conditions of complex on-site vibration processes, and are not operable and reproducible in on-site applications. Chinese patent CN114656184A proposes to improve the adsorption effect of admixtures on sulfate ions and enhance the sulfate resistant performance of concrete by adding barium carbonate and barium hydroxide. However, the large amount of barium salt added by this method is actually insoluble in water and has a slow reaction speed. It cannot effectively reduce the pores in the concrete at the early stage of concrete, and cannot guarantee the effectiveness of actual application. Summary of the invention

[0004] Purpose of the invention: The first purpose of the present invention is to provide a composite additive that significantly improves the crack resistance of concrete and improves its resistance to sulfate erosion; the second purpose of the present invention is to provide a concrete mixture that improves the resistance of concrete to sulfuric acid erosion at all ages; the third purpose of the present invention is to provide a method and application of the composite additive for preparing a concrete mixture.

[0005] Technical solution: The composite additive described in the present invention includes polyester fiber (PF), basalt fiber (BF) and calcium sulfoaluminate type expansion agent (U-type expansion agent), and the mass ratio of the polyester fiber (PF), basalt fiber (BF) and calcium sulfoaluminate type expansion agent (U-type expansion agent) is (1-1.5): (1-1.5): (2-4).

[0006] The concrete mixture of the present invention is prepared by mixing the composite additive with standard concrete components; the standard concrete components include at least one of fly ash and mineral powder, as well as cement, fine aggregate and coarse aggregate.

[0007] Preferably, the total mixing ratio of the composite additives in the concrete mixture is 0.6% to 1.5% of the total mass of the standard concrete components.

[0008] The method for preparing the concrete mixture of the present invention comprises the following steps:

[0009] (1) Dry mixing: First, dry mix cement, fly ash, mineral powder, and fine aggregate, then add half of the total amount of composite additives and mix, then add coarse aggregate and the other half of the composite additives and mix, and stir;

[0010] (2) Wet mixing: add water mixed with water reducer and stir;

[0011] (3) After curing, a concrete mixture is obtained.

[0012] Preferably, the specific operation of step (1) includes: pouring weighed cement, fly ash, mineral powder and fine aggregate into a mixer, adding half of the total amount of composite additives and continuing to stir for 30s to 120s to mix; pouring coarse aggregate and the other half of the composite additives and stirring for 30s to 120s to mix.

[0013] Preferably, the specific operation of step (2) includes: pouring water mixed with a water reducer and stirring for 60 to 120 seconds, wherein the lower the temperature, the longer the stirring time; after the stirring is completed, taking out some samples to test their working performance (slump, ductility), and discharging and forming if the requirements are met, otherwise continuing to stir until the requirements are met.

[0014] Preferably, the requirement is that the working performance of the concrete mixture meets the basic standards of the "Test Procedure for Hydraulic Concrete" (DL / T51502017).

[0015] Preferably, the specific operation of curing in step (3) includes: pouring the concrete mixture into a mold, vibrating to compact it, and curing it in a standard curing room for 28 to 32 days after demoulding; the curing conditions are room temperature (20±2)°C and relative humidity above 95%.

[0016] Application of the composite additive of the present invention in practical engineering.

[0017] The concrete mixture of the present invention is used in hydraulic concrete test.

[0018] Principle of the invention: The polyester fiber, basalt fiber and calcium sulfoaluminate expansion agent (U-type expansion agent) described in the present invention are all external admixtures. When preparing concrete, this new concrete composite additive is poured before adding water and stirring, so that the fiber and UEA expansion agent are evenly distributed inside the concrete, which can effectively improve the concrete's resistance to sulfate erosion and provide an accurate and reliable method for enhancing the strength and durability of concrete at different ages.

[0019] The addition of U-type expansion agent can compensate for the volume shrinkage of concrete and further improve the density and impermeability of concrete. Compared with plain concrete, the fibers inside the concrete mixed with fiber and U-type expansion agent (UEA) have a reinforcement effect after the specimen is poured, inhibiting the generation and development of cracks while also blocking the cracks, significantly reducing the connectivity of the pores inside the concrete and increasing the curvature of the permeability path. At the same time, the early micro-expansion effect of UEA itself, coupled with the fact that UEA can significantly increase the accumulation rate of the cement paste structure after 60 minutes, refines the pores of the concrete in the early curing stage of the specimen, that is, reduces the proportion of harmful pores and increases the proportion of harmless pores. Therefore, the impermeability and erosion resistance of the specimens mixed with appropriate amounts of fiber and UEA are significantly improved.

[0020] The beneficial effects of fiber and UEA on the strength development of concrete under sulfate attack can be attributed to the following reasons: 1. Fiber and UEA limit the expansion of the pores between concrete. With the addition of an appropriate amount of UEA and the accumulation of corrosion products, concrete expands, and the addition of fiber limits this expansion; 2. Fiber and UEA generate prestress inside concrete. During the hardening process of fiber and UEA composite materials, stress along the fiber direction is generated due to the action of the constraint force, thereby prestressing the fiber; 3. Fiber and UEA transmit compressive stress inside concrete. When the specimen is restricted to a certain volume during the corrosion process, the expansion constraint of concrete will generate compressive stress in the concrete, and then the compressive stress can be transmitted to the bonding surface of the fiber and concrete matrix, thereby further enhancing the bond between them. These comprehensive mechanisms also promote the overall performance of fiber UEA concrete hybrid materials when they are corroded. The addition of appropriate amounts of fiber and UEA can significantly improve the macroscopic deterioration process of concrete. Macro test data show that under the conditions of sulfate immersion-wet-dry cycle, adding an appropriate amount of fiber can alleviate the degradation rate of concrete macro performance, and the single addition of basalt fiber (BF) has an overall better effect on the specimen's resistance to sulfuric acid corrosion than the single addition of polyester fiber (PF); while the composite addition of fiber and U-type expansion agent (UEA) can significantly improve the appearance degradation of concrete and limit the quality loss, exerting a good synergistic effect and greatly alleviating salt corrosion damage. Among them, the composite addition of 0.15% BF and 0.4% UEA by mass of concrete has the best overall anti-corrosion performance.

[0021] Concrete is attacked by sulfate mainly in two ways: physical and chemical. The composite addition of fiber and expansion agent optimizes the microscopic pore structure of concrete matrix. The addition of appropriate amount of UEA can improve the fiber-matrix interface transition zone. The addition of fiber and UEA significantly improves the internal impermeability and corrosion resistance of the structure, which is a fundamental mechanism to improve the deterioration of concrete. The active and passive constraints of fiber and expansion agent play a synergistic effect, and the effectiveness of UEA is enhanced, and the anti-cracking effect of fiber is also improved. In summary, the new composite additive significantly improves the sulfate corrosion resistance of concrete by optimizing the pore structure and enhancing internal constraints.

[0022] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:

[0023] 1. The present invention significantly improves the crack resistance of concrete, reduces the generation of cracks, and improves the sulfate corrosion resistance by adding polyester fiber and basalt fiber.

[0024] 2. The present invention proposes a new preparation process for optimizing the distribution of aggregates in concrete mixtures. Through the new concrete mixture preparation method of "classification and multi-mixing", it can ensure that the components are fully mixed and evenly distributed, improve the uniformity and density of concrete, improve the comprehensive strength of concrete, reduce the strength variance of concrete, and improve the strength and sulfate corrosion resistance of concrete at all ages.

[0025] 3. The composite additive proposed in the present invention can effectively reduce the construction cost while ensuring that the concrete has the same anti-sulfate corrosion performance. Compared with the traditional anti-sulfate corrosion method, the composite additive and the method for preparing the concrete mixture of the present invention have lower cost, simpler construction, higher economy and practicality. While achieving the same effect of multi-age anti-sulfate corrosion performance concrete, the cost of engineering materials can be reduced by more than 50%.

[0026] 4. The preparation method of the composite additive and concrete mixture of the present invention has been used and verified in engineering practice, and is fully applicable to the preparation of general sulfate-resistant concrete. The sulfate corrosion resistance of concrete prepared by the preparation method is significantly improved. Under multiple dry-wet cycles and complex construction site conditions, the mass loss rate is reduced by more than 20%, and the concrete has good robustness. The preparation method of the composite additive and concrete mixture can provide ordinary concrete with internal materials that resist sulfate corrosion, which are integrated into the concrete, and help solve the problem that traditional concrete has poor sulfate corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The relationship diagram between the mass loss rate and the number of dry-wet cycles of concrete specimens with different mix ratios of the present invention;

[0028] Figure 2 This is a flow chart of the method for preparing a concrete mixture according to the present invention;

[0029] Figure 3 It is a schematic diagram of the pore structure change of the concrete mixture of the present invention under sulfate attack environment;

[0030] Figure 4 It is a schematic diagram of the corrosion of the plain concrete of the present invention;

[0031] Figure 5 This is a schematic diagram of the corrosion of fiber-added and UEA concrete of the present invention;

[0032] Figure 6 This is the microscopic combination effect of the fiber and the UEA-containing concrete of the present invention. DETAILED DESCRIPTION

[0033] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0034] The components in the specific implementation of the present application can all be obtained commercially. Among them, the cement is ordinary Portland cement of P·O 42.5 grade; the fine aggregate is artificial sand with a fineness modulus of 2.73; the coarse aggregate is divided into artificial aggregate, which is divided into 5-20mm small stones and 20-40mm medium stones, and the mass ratio of small stones to medium stones is 1:1. The water reducer is an ordinary polycarboxylic acid water reducer; the fly ash 45μm square hole sieve residue is 45% to 53%, the 28d strength activity index is 62-69%, and the CaO content in the chemical composition is 10% to 15%.

[0035] The present embodiment provides a sulfate-resistant concrete mixture, which includes the following components by weight: a water-cement ratio of 0.43, a mass ratio of cement, fly ash, mineral powder, coarse aggregate, and fine aggregate of 1:0.21:0.19:2.89:2.18; and a composite additive ratio of 0.6% to 1.5% of the total mass of the concrete.

[0036] Specifically, water 10.13kg, cement 15.6kg, fly ash 3.6kg, mineral powder 3.42kg, composite additives 14.4kg, fine aggregate 44.22kg, coarse aggregate 63.6kg, polycarboxylate water reducer 0.12kg;

[0037] The composite additive comprises the following components according to mass percentage: 15% to 30% of polyester fiber (PF), 15% to 30% of basalt fiber (BF), and 40% to 60% of calcium sulfoaluminate type expansion agent (U-type expansion agent).

[0038] This embodiment also provides a method for preparing a sulfate-resistant concrete mixture, comprising the following steps:

[0039] (1) Preparation of composite additives: Before preparing to mold and produce sulfate-resistant concrete, the composite additives are prepared first. First, polyester fiber (PF) and basalt fiber (BF) are evenly mixed in proportion as component A, and calcium sulfoaluminate type expansion agent (U-type expansion agent) is used alone as component B; component A and component B constitute the composite additive.

[0040] (2) weighing fine aggregate, cement, fly ash and mineral powder in proportion and putting them into a concrete mixer, then weighing 50% of the composite additive prepared in step (1) in proportion and adding them to the mixture for dry mixing for 30 to 120 seconds; weighing coarse aggregate in proportion and putting it into the concrete mixer, then weighing the remaining 50% of the composite additive prepared in step (1) in proportion and adding them to the mixture of aggregate, cement and fly ash for dry mixing for 30 to 120 seconds;

[0041] (3) adding polycarboxylate water-reducing agent and water to the mixture in step (2) in proportion, and stirring for 60 to 120 seconds (the lower the temperature, the longer the stirring time), thereby completing the mixing of the sulfate-resistant concrete;

[0042] (4) The mixed sulfate-resistant concrete shall be cured in accordance with the provisions of the "Test Procedure for Hydraulic Concrete" (DL / T51502017).

[0043] The following is an explanation through specific examples.

[0044] Example 1

[0045] Example 1 provides a concrete composite additive, which includes the following components in mass percentage: the mass ratio of the polyester fiber (PF), basalt fiber (BF) and calcium sulfoaluminate type expansion agent (U-type expansion agent) is: 1:1.5:4; specifically, 15% polyester fiber (PF), 25% basalt fiber (BF), and 60% calcium sulfoaluminate type expansion agent (U-type expansion agent).

[0046] Embodiment 1 also provides a sulfate corrosion resistant concrete mixture, comprising the following components:

[0047] 10.13kg water, 15.6kg cement, 3.6kg fly ash, 3.42kg mineral powder, 14.4kg composite additives, 44.22kg fine aggregate, 63.6kg coarse aggregate, and 0.12kg polycarboxylate water reducer.

[0048] Among them, between June and August (summer), the working temperature is between 25 and 40 degrees Celsius, and the mixing time of the mixture after wet mixing is 60 seconds according to the above-mentioned method for preparing a sulfate-resistant concrete mixture.

[0049] Example 2

[0050] The difference between Example 2 and Example 1 is that Example 2 provides a concrete composite additive, which includes the following components in mass percentage: the mass ratio of the polyester fiber (PF), basalt fiber (BF) and calcium sulfoaluminate type expansion agent (U-type expansion agent) is: 1:1:2; specifically, 25% polyester fiber (PF), 25% basalt fiber (BF), and 50% calcium sulfoaluminate type expansion agent (U-type expansion agent).

[0051] Embodiment 2 also provides a sulfate corrosion resistant concrete mixture, comprising the following components:

[0052] 10.13kg water, 15.6kg cement, 3.6kg fly ash, 3.42kg mineral powder, 14.4kg composite additives, 44.22kg fine aggregate, 63.6kg coarse aggregate, and 0.12kg polycarboxylate water reducer.

[0053] Among them, between September and November (autumn), the working temperature is between 10 and 25 degrees Celsius, and the mixing time of the mixture after wet mixing is 90 seconds according to the above-mentioned method for preparing sulfate-resistant concrete.

[0054] Example 3

[0055] The difference between Example 3 and Example 1 is that Example 3 provides a concrete composite additive, which includes the following components in mass percentage: the mass ratio of the polyester fiber (PF), basalt fiber (BF) and calcium sulfoaluminate type expansion agent (U-type expansion agent) is: 1.5:1.5:2; specifically, 30% polyester fiber (PF), 30% basalt fiber (BF), and 40% calcium sulfoaluminate type expansion agent (U-type expansion agent).

[0056] Embodiment 3 also provides a sulfate corrosion resistant concrete mixture, comprising the following components:

[0057] 10.13kg water, 15.6kg cement, 3.6kg fly ash, 3.42kg mineral powder, 14.4kg composite additives, 44.22kg fine aggregate, 63.6kg coarse aggregate, and 0.12kg polycarboxylate water reducer.

[0058] Among them, between December and February (winter), the working temperature is between -5 and 10 degrees Celsius, and the mixing time of the mixture after wet mixing is 120 seconds according to the above-mentioned method for preparing sulfate-resistant concrete.

[0059] Comparative Example 1

[0060] The difference between Comparative Example 1 and Example 1 is that the composite additive is 50% polyester fiber (PF) and 50% basalt fiber (BF), and there is no calcium sulfoaluminate type expansion agent (U-type expansion agent).

[0061] Comparative Example 2

[0062] The difference between Comparative Example 2 and Example 1 is that the composite additive is 100% calcium sulfoaluminate type expansion agent (U-type expansion agent), and lacks polyester fiber (PF) and basalt fiber (BF).

[0063] Performance Testing

[0064] The preparation and performance testing of the concrete of this embodiment and the comparative example were carried out in accordance with the "Concrete Compressive Strength Test Method", "Concrete Porosity Test Method" and "Concrete Mass Loss Test Method" specified in the "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete" (GB / T 50082-2009). The test results are shown in Table 1.

[0065] Table 1: Performance parameters of concrete in various examples

[0066] Example No. Compressive strength(MPa) Percentage of harmful pores (%) Mass loss (%) Example 1 48.5 47 7.82 Example 2 48.1 53 7.95 Example 3 47.75 59 8.44 Comparative Example 1 46.1 68 9.52 Comparative Example 2 46.7 77 8.96

[0067] According to the performance comparison of Examples 1-3 and Comparative Examples 1-2, the present application can effectively improve the compressive strength of concrete, reduce the harmful porosity and mass loss therein by adding polyester fiber, basalt fiber and U-type expansion agent in proportion. According to the performance comparison of Examples 1-3 and Comparative Example 1, the U-type expansion agent can compensate for the volume shrinkage of concrete, reduce internal pores, and improve the compactness and impermeability of concrete. During the concrete hardening process, the expansion effect of the U-type expansion agent can fill and seal the micropores inside the concrete, reducing the penetration of water and other corrosive media. According to the performance comparison of Examples 1-3 and Comparative Example 2, polyester fiber and basalt fiber can effectively control the formation of microcracks inside the concrete, alleviate the stress concentration phenomenon at the tip of the crack, and improve the flexural and splitting tensile strength of concrete. These fibers form a three-dimensional network structure in the concrete, which enhances the toughness and crack resistance of the concrete.

[0068] Furthermore, the present invention provides a new composite additive that can improve the sulfate corrosion resistance of concrete and a preparation method thereof. By optimizing the formula and preparation process, the sulfate corrosion resistance of concrete is significantly improved. The method has the advantages of low cost, simple construction, and superior performance, and has broad application prospects. Specifically, the compressive strength is significantly improved, the porosity is significantly reduced, and the mass loss is significantly reduced. These results show that the new composite additive can effectively improve the sulfate corrosion resistance of concrete, achieving the sulfate corrosion resistance effect of concrete prepared with medium-sulfur-resistant cement, and its preparation cost is low, easy to promote and apply, and is suitable for engineering construction in high-sulfate areas.

[0069] The mass loss of specimens with different ratios in the corresponding sulfate dry-wet cycle is shown in the figure below. Figure 1As shown. CO represents the benchmark group specimen. The letters P, B and PB in the specimen number represent single-doped PF, BF and mixed PF, BF (mixed ratio is 1:1), respectively, and the numbers represent the volume content of fiber in concrete. The letter 4U means that 0.4% (in terms of cementitious material) UEA is added to the original P, B and PB mix ratio. It can be seen from the figure that the mass change law of specimens with different ratios is consistent. With the increase of the number of sulfate dry-wet cycles, the mass loss rate of the specimen shows a law of first decreasing and then increasing, which means that the mass of the specimen has undergone a process of first increasing and then decreasing. During the entire erosion process, the mass loss rate can be roughly divided into the stages of decline-rapid rise-slow rise.

[0070] When the number of dry-wet cycles was 10, the mass loss rate of all specimens decreased, which was mainly due to the accumulation of sulfate erosion crystal products inside them, and the quality was improved. As the number of dry-wet cycles increased from 10 to 40 times, the mass loss rate of the specimens increased rapidly. This was mainly because with the increase in the number of dry-wet cycles, new erosion paths emerged and expanded, erosion products continued to accumulate in the pores, cracks gradually widened, and the corners of the specimens gradually disappeared, which led to the specimens falling off, so the quality decreased rapidly. After the number of dry-wet cycles exceeded 40 to 50 times, the increase in the mass loss rate of the specimens decreased. This was because under the continuous erosion of the concrete specimens, the outer layer of the specimens, the "shell", gradually fell off, and the fresh structure inside was exposed to the erosion solution. This part of the structure was relatively dense, and the erosion ions reacted with the new structure to form new crystals, which would re-block the larger pores in the concrete specimen matrix, causing the mass loss rate of the concrete to decrease slightly in the later period.

[0071] In addition, the test also shows that sulfate erosion does not have a significant effect on the quality of concrete specimens before the number of cycles reaches 20. As the number of dry-wet cycles of sulfuric acid increases, the degree of erosion deepens, and the addition of fibers has a significant improvement on the mass loss of concrete. When the number of cycles reaches 50, the mass loss rate of the CO group specimens has reached 9.52%, while the P0.1, B0.15 and PB0.15 groups are 7.90%, 7.72% and 7.81% respectively. The composite addition of fiber and 0.4% UEA can more effectively alleviate the mass loss degradation of the specimens, and its mass loss rate is only 6.12% to 7.77%. In general, the composite addition of fiber and UEA, on the one hand, the expansion filling of UEA makes the interior of the concrete denser and reduces the production of erosion products; on the other hand, the fiber plays a pulling and bridging role, effectively restrains the extension of cracks, and reduces the incidence of slurry shell and matrix shedding.

[0072] The porosity and pore size distribution of the CO, B0.15 and B0.15-4U groups were determined by AutoPore V mercury intrusion instrument before and after sulfate immersion-wet-dry cycle. Based on the existing pore structure theory proposed by Academician Wu Zhongwei in his early years, combined with the distribution of pore structure (such as Figure 3 As shown in the figure, the internal pore size of the concrete specimen is divided into harmless fine pores (0-0.1μm), low-harm small pores (0.1-1μm), harmful small and medium pores (1-10μm), and harmful medium and large pores (10-100μm).

[0073] from Figure 3 (a) to (c) show that under the sulfate attack mode of salt immersion-wet-dry cycle, the degradation of pore structure is mainly due to the invasion of sulfate, the formation of new micropores, the gradual enlargement of small pores, the degradation of relatively harmful small and medium pores, and the expansion of medium and large pores into cracks, which damages the internal structure of concrete and weakens its strength. Figure 3 It can be seen from (d) that the proportion of harmless pores in the specimen first increases slightly and then decreases with the increase in the number of dry-wet cycles, while the proportion of harmful pores first decreases and then increases. This is because the generation of hydration products and corrosion products in the early concrete fills the larger pores in the specimen, but with the increase of corrosion products, the pores are gradually expanded, and the proportion of low-harm pores, harmful pores and hazardous pores gradually increases. The larger the cumulative pore volume, the more serious the strength loss. Before the start of the sulfate erosion test, the proportion of harmless pores of the specimens was 51.16%, 55.19% and 58.64%, respectively, the proportion of low-harmful pores was 33.27%, 32.23% and 31.02%, respectively, the proportion of harmful pores was 10.65%, 8.82% and 7.33%, respectively, and the proportion of hazardous pores was 4.92%, 3.76% and 3.01%, respectively; based on the pore data of 0 dry-wet cycles, after 50 salt immersion-dry-wet cycles, the proportion of harmless pores of the specimens decreased by 10.00, 7.10 and 5.55 percentage points, respectively, the proportion of low-harmful pores increased by 4.08, 2.13 and 2.05 percentage points, respectively, the proportion of harmful pores increased by 3.01, 2.26 and 2.20 percentage points, respectively, and the proportion of hazardous pores increased by 2.91, 2.83 and 1.20 percentage points, respectively.

[0074] In general, the macro-experimental analysis can conclude that the addition of fiber and UEA can increase the proportion of tiny harmless pores, reduce the content of medium and large harmful and hazardous pores, optimize the internal pore structure of concrete, and thus improve the concrete's resistance to sulfate erosion. In addition, the joint addition of appropriate amounts of fiber and UEA is more advantageous for the refinement of the early concrete pore structure and can reduce the deterioration rate.

[0075] Relevant studies have shown that the number of corrosion products and the pore structure of concrete are two key factors that determine its resistance to sulfate corrosion. Among them, the pore structure plays a greater role in long-term resistance to sulfate corrosion. The pore structure is closely related to the permeability of concrete. The complexity of the pore structure determines the complexity of its water permeability. Therefore, the durability of concrete depends on the evolution of the pore structure. The capillaries control the transport performance and durability of concrete. The pore structure parameters such as capillary porosity, tortuosity, and connectivity determine the penetration rate of the solution, which seriously affects the SO4 2- When the porosity is high, the capillary pores and gel pores are interconnected to form a network structure, and the permeability of the concrete is greatly improved. According to the above erosion principle, the chemical erosion expansion effect mainly comes from the hydration of external invading sulfate ions and the expansion components in the concrete to form products such as calcium sulfonate and gypsum. After solidification, the volume of the hardened paste increases, resulting in expansion.

[0076] like Figure 4 and Figure 5 As shown in the figure, compared with plain concrete, the fibers in the concrete mixed with fiber and UEA played a reinforcing effect after the specimen was poured, inhibiting the generation and development of cracks while also blocking the cracks, significantly reducing the connectivity of the pores inside the concrete and increasing the curvature of the permeation path. At the same time, the micro-expansion effect of UEA itself in the early stage, coupled with the addition of UEA, can significantly increase the structural stacking rate of the cement paste after 60 minutes, and refine the pores of the concrete in the early curing stage of the specimen, that is, reduce the proportion of harmful pores and increase the proportion of harmless pores. Therefore, the impermeability and erosion resistance of the specimen mixed with appropriate amounts of fiber and UEA are significantly improved.

[0077] The beneficial effects of fiber and UEA on the strength development of concrete under sulfate attack can be attributed to the following reasons: first, the addition of fiber limits the expansion of concrete due to the addition of appropriate amount of UEA and the accumulation of attack products; second, during the hardening process of fiber and UEA composites, stresses are generated along the fiber direction due to the action of restraint force, thereby prestressing the fibers; third, when the specimen is confined to a certain volume during the attack process, the expansion constraint of concrete will generate compressive stress in the concrete, which can then be transferred to the interface between the fiber and concrete matrix, thereby further enhancing the bond between them. These combined mechanisms simultaneously promote the overall performance of fiber-UEA concrete hybrids under attack.

[0078] In order to explain the above synergistic effect more intuitively, SEM images of the fibers and the UEA-containing concrete matrix of Example 1 of the present invention were taken at a magnification of 5000 times. Figure 6As shown in the figure, it can be seen that UEA makes the gap of the fiber-matrix interface smaller and the interface transition smoother. When UEA self-expands, it will generate compressive force on the fiber, thereby reducing the gap in the interface transition zone and providing a certain stress around the fiber, thereby optimizing the interface bonding. Adding an appropriate amount of UEA can improve the adhesion of the fiber. The synergistic effect occurs because the fiber can convert expansion and self-expansion into passive constraints, during which the effectiveness of UEA is enhanced, and UEA provides self-expansion by triggering active constraints, while the gain effect of the fiber is also improved.

Claims

1. A composite additive, characterized in that: The invention comprises polyester fiber (PF), basalt fiber (BF) and calcium sulfoaluminate type expansion agent (U-type expansion agent), wherein the mass ratio of the polyester fiber (PF), basalt fiber (BF) and calcium sulfoaluminate type expansion agent (U-type expansion agent) is (1-1.5): (1-1.5): (2-4).

2. A concrete mixture, characterized in that: The composite additive according to claim 1 is mixed with standard concrete components; the standard concrete components include at least one of fly ash and mineral powder, as well as cement, fine aggregate and coarse aggregate.

3. The concrete mixture according to claim 2, characterized in that: The total mixing ratio of the composite additive is 0.6% to 1.5% of the total mass of the standard concrete components.

4. A method for preparing the concrete mixture according to claim 2, characterized in that: The following steps are involved: (1) Dry mixing: First, dry mix cement, fly ash, mineral powder, and fine aggregate, then add half of the total amount of composite additives and mix, then add coarse aggregate and the other half of the composite additives and mix, and stir; (2) Wet mixing: add water mixed with water reducer and stir; (3) After curing, a concrete mixture is obtained.

5. The method for preparing a concrete mixture according to claim 4, characterized in that: The specific operation of step (1) includes: pouring weighed cement, fly ash, mineral powder and fine aggregate into a mixer, adding half of the total amount of composite additives and continuing to stir for 30s to 120s to mix; pouring coarse aggregate and the other half of the composite additives and stirring for 30s to 120s to mix.

6. The method for preparing a concrete mixture according to claim 4, characterized in that: The specific operation of step (2) includes: pouring water mixed with a water reducing agent and stirring for 60 to 120 seconds; taking out some samples after the stirring to test their working performance (slump, ductility), if the requirements are met, discharging and forming, otherwise continue stirring until the requirements are met.

7. The method for preparing a concrete mixture according to claim 6, characterized in that: The requirement is that the working performance of the concrete mixture meets the basic standards of the "Test Procedure for Hydraulic Concrete" (DL / T 51502017).

8. The method for preparing a concrete mixture according to claim 4, characterized in that: The specific operation of curing in step (3) includes: pouring the concrete mixture into a mold, vibrating and compacting it, and curing it in a standard curing room for 28 to 32 days after demoulding; the curing conditions are room temperature (20±2)°C and relative humidity above 95%.

9. Application of the composite additive according to claim 1 in practical engineering.

10. Use of the concrete mixture according to claim 2 or 3 or the concrete mixture prepared by any preparation method of claims 4 to 8 in hydraulic concrete testing.

Citation Information

Patent Citations

  • Sulfate-erosion-resistant concrete admixture, preparation method thereof and concrete

    CN114656184A

  • Sulfate-erosion-resistant plant fiber concrete and preparation method thereof

    CN116535151A

  • Preparation method of sulfate-erosion-resistant concrete

    CN118005365A

  • Sulfate-erosion-resistant concrete and preparation method thereof

    CN118388183A